Embalaje sin fondo - Sierralta Ríos, Aníbal (1993)
This case is aimed at international trade operators, production managers and students of Administration and Marketing; its purpose is to help them put into practice their knowledge of packaging, quality control and international marketing of tropical products, allowing them to learn the basic elements of international standardization. This is a real-life case and can be applied to any Latin American country, it highlights the importance of quality control systems and international standardization to reduce costs. In addition, even though it is not its main objective, it shows the demands of developed countries that are show in the form of technical barriers.